Rheological characterization of EVAK components for hot melt adhesives formulation - Šiška, Bedřich; Machač, Ivan; Balcar, Miroslav; Vrána, Jiří (University of Pardubice, 2012)
For formulation of hot melt adhesives, ethylene-vinyl acetate copolymers (EVAK) are most commonly used. In this paper, the results of measurements of mechanical and rheological properties of three EVAK components of various melt indexes are presented. These properties were studied under the steady shear and dynamic conditions using a DMA analyser and a Haake MARS rheometer. From the DMA experimental data, the glass transition temperatures of EVAK components were determined. On the rheometer MARS, the measurements of flow curves, primary normal stress differences, oscillatory and creep & recovery tests of melted samples were performed.